Consolidation of the road freight transport industry in the Far Eastern Federal District: In search of strategic priorities for the development of the transport and logistics industry - Tyurina, Elena; Gagarin, Daniil; Dolbin, Vladimir; Filatov, Alexander; Chulskiy, Semyon (Edelweiss Applied Science and Technology, 2026)
The study examines consolidation in the road freight transport industry of the Far Eastern Federal District (FEFD) with the aim of identifying strategic priorities for the development of the regional transport and logistics sector. The analysis combines a structured five-stage framework for market assessment with qualitative methods, including case studies of mergers and acquisitions, expert interviews, and media content analysis, to evaluate market boundaries, concentration, consolidation drivers, and their effects. Market concentration is measured using standard indices such as concentration ratios and the Herfindahl–Hirschman Index, showing a fragmented industry without dominant firms, where increased concentration is unlikely to reduce welfare and may instead enhance efficiency through economies of scale and reduced duplication of fixed costs. The study demonstrates that consolidation can lower transport costs, improve asset utilization, and contribute to environmental goals by decreasing the number of trips and associated carbon emissions. The findings highlight three main outcomes of consolidation: strengthening the investment attractiveness of the macro-region, supporting the transition to greener logistics, and increasing fiscal transparency in the road freight segment. Based on this, the research proposes two key strategic priorities for the FEFD: digitalization of logistics processes, including the deployment of intelligent transport systems and electronic document management, and the development of international transport corridors.